240-250 Washington Street, ca. 1859 - Unknown (Tufts Archival Research Center, 2005)
Elevated view south-southwest (left to right) of 240-250 Washington Street, located between Central Court to the east-northeast and Avon Place to the west-southwest. Signage and awnings adorn the facades of the buildings, which face north-northwest. A street light is located on the corner of Central Court and Washington Street. 244 Wasington Street the former home of Chief Justice Samuel Sewall, built 1693; later residence and shop of Isiah Thomas, printer 8 x 6 1/8, 10 x 8 overall Albumen prints